Preparation, characterization and in vitro release studies of insulin-loaded double-walled poly(lactide-co-glycolide) microspheres - Ansary, Md. Rezaul Haque; Rahman, Md. Mokhlesur; Awang, Mohamed; Katas, Haliza; Ab. Hadi, Hazrina; Abd Almonem, Doolaanea (Springer, 2016)
The purpose of this study was to fabricate insulin-loaded double-walled and singlepolymer poly(lactide-co-glycolide) (PLGA) microspheres using a fast degrading glucose core, hydroxyl-terminated poly(lactide-co-glycolide) (Glu-PLGA) and a moderate degrading carboxyl-terminated PLGA polymers. A modified water-in-oil-in-oilin-water (w/o/o/w) emulsion solvent evaporation technique was employed to prepare double-walled microspheres, whereas single-polymer microspheres were fabricated by a conventional water-in-oil-in-water (w/o/w) emulsion solvent evaporation method. The effect of fabrication techniques and polymer characteristics on microspheres size,morphology, encapsulation efficiency, in vitro release and insulin stability were evaluated. The prepared double-walled microspheres were essentially non-porous,smooth surfaced, and spherical in shape, whereas single-polymer microspheres were highly porous. Double-walled microspheres exhibited a significantly reduced initial burst followed by sustained and almost complete release of insulin compared to singlepolymer microspheres. Initial burst release was further suppressed from double-walled microspheres when the mass ratio of the component polymers was increased. In conclusion, double-walled microspheres made of Glu-PLGA and PLGA can be a potential delivery system of therapeutic insulin.